Evaluation of Pile Cap Reinforcement Design Using Conventional and Finite Element with Strut and The Method Based on SNI 2847-2019 - Fajri Yusmar; Isda, Raiyyan Rahmi (Rekayasa Sipil, 2024)
The Strut and Tie Method (STM) is one effective method for predicting the ultimate strength, failure modes, and behavior of reinforced concrete pile caps. However, the use of the strut and tie method in pile cap design in Indonesia is not as popular as the use of conventional methods. This study aims to evaluate the reinforcement design of pile caps using conventional methods and the finite element method (FEM) approach, utilizing the strut and tie method specified in SNI 2847 2019. The analysis results show that the required area of longitudinal reinforcement in the conventional method does not meet the criteria when evaluated using the STM method. The deficiency in the longitudinal reinforcement area amounts to 40.13% compared to the design results obtained using the STM method. Meanwhile, the use of the FEM method results in a required reinforcement area that exceeds the required area for the STM method. The difference in reinforcement is even greater, reaching up to 7.85% for the FEM method.